Analysis of Factors Influencing the Interest in Making Islamic Mutual Fund Investments Among Muslims of Malang City - Padang, Yusman Ahmad Muzakki; Muttaqin, Aminullah Achmad (Islamic Economics and finance in Focus, 2025)
The study aims to analyze the influence of sharia financial literacy, technological advancement, and income level on the investment interest of the muslim community in Malang City toward islamic mutual fund. The background of this research is based on the phenomenon that considerable portion of the muslim community still allocates their funds to conventional mutual funds, which in practice may contain elements that are inconsistent with sharia principle. Using a quantitative approach, data was collected by distributing questionnaires through google form which will involve respondents from the people of Malang City that fulfill the criteria. The data were analyzed using the Partial Least Squares Structural Equation Modelling method, which includes testing the measurement model and examining the casual relationship among latent constructs within the structutal model. The results indicate that islamic financial literacy, technological advancement, and income have a positive influence on the interest in investing in islamic mutual funds among the Muslim community in Malang City. The findings are expected to provide valuable insights for stakeholders in the islamic capital market industry in designing effective strategies to enhance muslim community interest in islamic mutual funs products.